2012
DOI: 10.2478/v10247-012-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser priming on canola yield and its components under salt stress

Abstract: A b s t r a c t. The effect of laser priming at different irradiation times on canola yield and its components under saline conditions were investigated. The results showed that laser priming had a positive effect on yield and its components and caused yield increase under saline conditions. Increase in salt levels had a negative and significant effect on seed yield, number of seeds per pod, number of pod per plant, pod length and plant height. The results showed that 45-min laser priming had the strongest eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…Reduced plant height caused by saline stress is caused by reduced osmotic and leaf water potential, and increased electrolyte leakage (Dolatabadi and Toorchi, 2017). Salt stress negatively impacted canola seed germination (Mahmoodzadeh, 2008), radicle and plumule length and seedling fresh weight (Bybordi and Tabatabaei, 2009;Bybordi, 2010a), reduced biomass (Bybordi, 2010b), inhibited the seed-filling phase, reduced the number of seeds per pod, number of pods per plant, pod length and plant height (Zamani et al, 2010;Mohammadi et al, 2012), formed fewer leaves, branches, flowers, siliques, shorter siliques, and fewer seed per silique and 1000-seed weight (Mahmoodzadeh, 2008), reduced leaf size and nutrient absorption levels of leaves (Shainberg and Shalhevet, 2012), reduced root, hypocotyl and leaf growth in seedlings with a concomitant rise in IAA oxidase and peroxidase activity (Bybordi et al, 2010a), reduced chl a, chl b and total chl content (Nazarbeygi et al, 2011;Bahrani, 2013), reduced total fatty acids by 25% (Bybordi et al, 2010b), reduced dry matter, plant height, seed yield and 1000-seed weight (Shabani et al, 2013), and reduced root length, seedling fresh weight, seedling dry weight, RWC, ion leakage and chl content in seedlings of five cowpea cultivars (El-Shaieny, 2015). The decrease in chl content as salinity increased resulted in lower dry weight and reduced leaf area, but this reduction in leaf area and plant height did not occur in salt-resistant canola cultivars (Kamrani et al, 2013).…”
Section: Effect Of Salinity Stress On Canola Growth and Productivitymentioning
confidence: 99%
“…Reduced plant height caused by saline stress is caused by reduced osmotic and leaf water potential, and increased electrolyte leakage (Dolatabadi and Toorchi, 2017). Salt stress negatively impacted canola seed germination (Mahmoodzadeh, 2008), radicle and plumule length and seedling fresh weight (Bybordi and Tabatabaei, 2009;Bybordi, 2010a), reduced biomass (Bybordi, 2010b), inhibited the seed-filling phase, reduced the number of seeds per pod, number of pods per plant, pod length and plant height (Zamani et al, 2010;Mohammadi et al, 2012), formed fewer leaves, branches, flowers, siliques, shorter siliques, and fewer seed per silique and 1000-seed weight (Mahmoodzadeh, 2008), reduced leaf size and nutrient absorption levels of leaves (Shainberg and Shalhevet, 2012), reduced root, hypocotyl and leaf growth in seedlings with a concomitant rise in IAA oxidase and peroxidase activity (Bybordi et al, 2010a), reduced chl a, chl b and total chl content (Nazarbeygi et al, 2011;Bahrani, 2013), reduced total fatty acids by 25% (Bybordi et al, 2010b), reduced dry matter, plant height, seed yield and 1000-seed weight (Shabani et al, 2013), and reduced root length, seedling fresh weight, seedling dry weight, RWC, ion leakage and chl content in seedlings of five cowpea cultivars (El-Shaieny, 2015). The decrease in chl content as salinity increased resulted in lower dry weight and reduced leaf area, but this reduction in leaf area and plant height did not occur in salt-resistant canola cultivars (Kamrani et al, 2013).…”
Section: Effect Of Salinity Stress On Canola Growth and Productivitymentioning
confidence: 99%
“…San Juan hybrid presented its maximum yield with an exposure time of 6 min (plus 6.52%), equivalent to an increment of 600 kg ha -1 of grain. Hybrid response to electromagnetic irradiation was similar to the one observed in maize seedlings by Hernández et al (2009); there is, however, little information about the effect of electromagnetic field on maize growth and production; in crops like canola, an increase of seed yield per pod was observed (Mohammadi et al, 2012) and higher yield in wheat, 12.5 and 14.5% (Pietruszewski and Kania, 2010).…”
Section: Interaction Of Corn Hybrids × Time Of Exposure To Electromagmentioning
confidence: 58%
“…In mushrooms under the same conditions, fresh weight and dry matter increased by 76.42 and 38.26%, and the days to head appearance were reduced by 26.86% ; in pea, length and dry weight of seedlings increased by 140.5 and 91.3% . Mohammadi et al (2012) observed that canola seed exposed to laser radiation during 45 min showed significant effect on seed yield per pod and reduction of the impact of salt stress in soil. Higher accumulation of dry matter and sugar content, compared to the non-irradiated plants was observed, when radiating sugar beet seed with laser at pre-sowing (Sacala et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…The variations of temperature will be a function of the seed characteristics, as well as the exposure time to the laser beam (Hernandez et al, 2010). The exposure times to red laser irradiation (wavelength from 618 to 780 nm) have ranged from milliseconds, seconds, minutes to hours using several lasers (Aladjadjiyan, 2012;Hoseini et al, 2013;Khalifa and Ghandoor, 2011;Metwally et al, 2013;Mohammadi et al, 2012;Podleśny et al, 2012). Therefore, the objective of the present study was to determine the evolution of the temperature in maize seeds (Zea mays L.) when LILI was applied during 60 s and after 60 s of laser off, evaluating the temperature variation by using a thermal camera.…”
Section: Introductionmentioning
confidence: 99%